2014
DOI: 10.1371/journal.pone.0092553
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Copy Number Variation and Genome-Wide Expression Profiling in Colorectal Cancer Tissues

Abstract: Integrative analyses of multiple genomic datasets for selected samples can provide better insight into the overall data and can enhance our knowledge of cancer. The objective of this study was to elucidate the association between copy number variation (CNV) and gene expression in colorectal cancer (CRC) samples and their corresponding non-cancerous tissues. Sixty-four paired CRC samples from the same patients were subjected to CNV profiling using the Illumina HumanOmni1-Quad assay, and validation was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 52 publications
(55 reference statements)
3
53
0
Order By: Relevance
“…Previous study using whole genome copy number variation (CNV) analysis revealed that the EMILIN3 gene was significantly increased in copy number in colorectal cancer samples as compared to non-cancerous samples [37]. However, the role of EMILIN3 in gliomas remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study using whole genome copy number variation (CNV) analysis revealed that the EMILIN3 gene was significantly increased in copy number in colorectal cancer samples as compared to non-cancerous samples [37]. However, the role of EMILIN3 in gliomas remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CHD6 is found at intranuclear sites of mRNA synthesis (43) and operates as a coactivator for the cellular Nrf2 transcription factor (61). Very little is known of CHD6 function, although reports suggest its involvement in processes such as human cancers (62)(63)(64). Mutations in the CHD7 gene are described as responsible for CHARGE syndrome, a complex neurological syndrome (65); since it interacts with CHD7, CHD8 might also be involved in CHARGE syndrome (66).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling could identify involved genes within large gain regions; however, there could be discrepancies between the degree of structural variation and gene expression levels [1,26,27]. Gene expression profiling has discovered novel cancer genes whose induction mechanisms are independent of CNVs [27].…”
Section: Future Directionsmentioning
confidence: 99%